Model Altman Untuk Menilai Kinerja Perusahaan Subsektor Pertambangan Batubara Periode 2015-2019 - Munandar, Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to determine the degree of accuracy of the Altman Z-score method in predicting the bankruptcy of a company. This study uses quantitative research with a descriptive approach through accuracy and error type tests. Where the samples used are companies that are members of the coal mining sub-sector during the 2015-2019 period. Purposive sampling method was used in sampling with a total sample of 19 companies. The Altman Z-score method has an accuracy rate and type error of 11% and 42%, which indicate that the method is not good for use in companies that are members of the coal mining sub-sector.